2019
DOI: 10.1101/766089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A locked immunometabolic switch underlies TREM2 R47H loss of function in human iPSC--derived microglia

Abstract: Loss‐of‐function genetic variants of triggering receptor expressed on myeloid cells 2 (TREM2) are linked with an enhanced risk of developing dementias. Microglia, the resident immune cell of the brain, express TREM2, and microglial responses are implicated in dementia pathways. In a normal surveillance state, microglia use oxidative phosphorylation for their energy supply, but rely on the ability to undergo a metabolic switch to glycolysis to allow them to perform rapid plastic responses. We investigated the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…Also, APOE ε4/ε4 cells displayed impaired uptake of extracellular Aβ42, impaired chemokinesis, impaired phagocytosis of zymosan‐coated beads, and deficits in both mitochondrial respiratory capacity and glycolytic capacity 42,63 (and our unpublished data) when compared to APOE ε3/ε3 cells. Similar metabolic deficits were observed in iPSC‐derived microglia‐like cells carrying the missense TREM2 mutations associated with different forms of dementia, including AD, FTD, and Nasu‐Hakola disease 41,64 . These deficits could be partially rescued by treatment with pioglitazone, a potent agonist of PPARγ, 41 and are consistent with Nanostring transcriptomics analysis of parietal cortex of human AD patients showing that the brains carrying TREM2 R47H mutation displayed elevated expression of genes involved in oxidative stress and lipid metabolism, along with a decreased expression of the genes involved in autophagy, growth‐factor signaling, and neural connectivity 65 .…”
Section: Microgliasupporting
confidence: 56%
See 1 more Smart Citation
“…Also, APOE ε4/ε4 cells displayed impaired uptake of extracellular Aβ42, impaired chemokinesis, impaired phagocytosis of zymosan‐coated beads, and deficits in both mitochondrial respiratory capacity and glycolytic capacity 42,63 (and our unpublished data) when compared to APOE ε3/ε3 cells. Similar metabolic deficits were observed in iPSC‐derived microglia‐like cells carrying the missense TREM2 mutations associated with different forms of dementia, including AD, FTD, and Nasu‐Hakola disease 41,64 . These deficits could be partially rescued by treatment with pioglitazone, a potent agonist of PPARγ, 41 and are consistent with Nanostring transcriptomics analysis of parietal cortex of human AD patients showing that the brains carrying TREM2 R47H mutation displayed elevated expression of genes involved in oxidative stress and lipid metabolism, along with a decreased expression of the genes involved in autophagy, growth‐factor signaling, and neural connectivity 65 .…”
Section: Microgliasupporting
confidence: 56%
“…Similar metabolic deficits were observed in iPSC‐derived microglia‐like cells carrying the missense TREM2 mutations associated with different forms of dementia, including AD, FTD, and Nasu‐Hakola disease 41,64 . These deficits could be partially rescued by treatment with pioglitazone, a potent agonist of PPARγ, 41 and are consistent with Nanostring transcriptomics analysis of parietal cortex of human AD patients showing that the brains carrying TREM2 R47H mutation displayed elevated expression of genes involved in oxidative stress and lipid metabolism, along with a decreased expression of the genes involved in autophagy, growth‐factor signaling, and neural connectivity 65 . Also, another immunohistochemical study showed the accumulation of autophagosomes inside microglia in AD brains with TREM2 mutations 66 .…”
Section: Microgliasupporting
confidence: 56%
“…Some TREM2 loss-of-function-related phenotypes in the context of AD were recently described by others in iPSC-derived microglia ( 42 45 ). While the literature about iPSC microglia is growing, more descriptions are needed to compare different approaches that generate robust and scalable human cellular models of microglia.…”
Section: Introductionmentioning
confidence: 83%
“…The iPSC technology together with the evolving understanding of microglial origin in mice and humans ( 21 23 ) allow now the robust generation of human iPSC-derived microglia-like cells ( 24 26 , 78 ) in large amounts ( 25 , 27 ).This provides the opportunity to employ human iPSC microglia for large-scale drug screening and for extensively studying biological mechanisms under more physiological and translational conditions. Additionally, iPSC based models provide the opportunity to study the effect of disease associated genes with isogenic mutation or knockout pairs ( 42 , 43 , 45 ). All of these protocols aim to follow the course of embryonic development and to recapitulate this in vitro as far as possible ( 24 27 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages exposed to extracellular pathogenic lipids can activate a triggering receptor expressed on myeloid cells 2 (TREM2)‐dependent gene response involved in phagocytosis and lipid catabolism 186,187 . TREM2 expression is required for a metabolic switch towards glycolysis and is essential for the maintenance of healthy energy metabolism under conditions of stress 90,188 . TREM2 signalling also drives the formation of lipid‐associated macrophages (LAM) in adipose tissue.…”
Section: We Are What We Eat: Immunometabolism Of Macrophagesmentioning
confidence: 99%